1993
DOI: 10.1107/s0108767392009863
|View full text |Cite
|
Sign up to set email alerts
|

On the relation between the diffraction ratio, the doublet values and the reliability of the triplet estimates

Abstract: A diffraction ratio is proposed that predicts the differences to be expected between the intensities of two-isomorphous data sets. This ratio is important for the ab initio structure determination of isomor-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…An important goal of the paper is the derivation of a new expression to estimate the triplet phase sums present among isomorphous data. It will be shown that the new procedure, supplemented by optimal doublet phase-sum estimates that use difference Patterson information [Kyriakidis, Peschar & Schenk (1993b), from now on referred to as KPS2], leads to far better results than obtainable by other j.p.d.-based expressions (Hauptman, 1982a, b;Giacovazzo, 1983;Giacovazzo, Cascarano & Zheng, 1988;Fortier & Nigam, 1989;Peschar & Schenk, 1991;hereafter P&S), in particular if the DR is small (Kyriakidis, Peschar & Schenk, 1993a; from now on KPS 1). In contrast with other DM techniques, the final triplet distributions in the SAS and 2DW cases seem to be of sufficient quality to be used in a normal DM procedure.…”
Section: Introductionmentioning
confidence: 99%
“…An important goal of the paper is the derivation of a new expression to estimate the triplet phase sums present among isomorphous data. It will be shown that the new procedure, supplemented by optimal doublet phase-sum estimates that use difference Patterson information [Kyriakidis, Peschar & Schenk (1993b), from now on referred to as KPS2], leads to far better results than obtainable by other j.p.d.-based expressions (Hauptman, 1982a, b;Giacovazzo, 1983;Giacovazzo, Cascarano & Zheng, 1988;Fortier & Nigam, 1989;Peschar & Schenk, 1991;hereafter P&S), in particular if the DR is small (Kyriakidis, Peschar & Schenk, 1993a; from now on KPS 1). In contrast with other DM techniques, the final triplet distributions in the SAS and 2DW cases seem to be of sufficient quality to be used in a normal DM procedure.…”
Section: Introductionmentioning
confidence: 99%
“…In the PDB release of July 1991, this structure is referred to as 155C. Tables 2 to 11 employed Doublet estimation using probabilistic technique (mode) Doublet estimation using probabilistic technique (numerical) Doublet estimation using algebraic technique Doublet estimation using difference Patterson synthesis The doublet estimates are equal to zero The doublet estimates are equal to the true doublet values Reflection with indices hkl Diffraction ratio (Kyriakidis, Peschar & Schenk, 1993) E values from the first data set E values from the second data set Reliability factor of the distribution (Peschar & Schenk, 1991) Number of the triplets involved in the statistics* Mean absolute doublet (triplet) error in mc [equations (22a), (23a)] Mean doublet (triplet) error in mc [equations (22b), (23b)] * Instead of one triplet (Cochran distribution), eight isomorphous triplets exist because of the distribution involving two isomorphous data sets. Hence, the real number of triplets involved in the statistics is eight times the NTR.…”
Section: Test Results and Discussionmentioning
confidence: 99%
“…The first column indicates the relevant technique (SAS, SIRNAS, SIRAS and 2DW). The second column lists the theoretical DR (Kyriakidis, Peschar & Schenk, 1993) and columns 3 to 12 show the error in mc (1000mc= 2~ rad) of the mean absolute difference, AER, AER = (I I ~,7"ltru¢-I ~,7"l~s, [>, (22a) and of the mean difference, ERR, Table 5 illustrate the strength of ALG compared with the JPD estimation. The improved algebraic estimation PAT gives the same results as the normal algebraic estimation ALG since the two data sets differ only in one pair of non-identical anomalous scatterers so the double summation in (14) is not expected to contribute considerably.…”
Section: Test Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional advantage of the difference-structure-factor approach is that the mathematical calculations are simplified. It has been shown for calculated structure-factor data that, by taking the F~ a as a random variable, reliable estimates of the triplet phase sums present among isomorphous data sets can be obtained, even if the diffraction ratio is small (Kyriakidis, Peschar & Schenk, 1993a). An additional improvement is achieved by supplementing the estimation of the doublet phase sums with vectors from a difference Patterson synthesis (Kyriakidis, Peschar & Schenk, 1993b,c).…”
Section: Introductionmentioning
confidence: 99%